Development of 5-hydroxypyrazole derivatives as reversible inhibitors of lysine specific demethylase 1. Issue 14 (15th July 2017) - Mould, Daniel P.; Bremberg, Ulf; Jordan, Allan M.; Geitmann, Matthis; Maiques-Diaz, Alba; McGonagle, Alison E.; Small, Helen F.; Somervaille, Tim C.P.; Ogilvie, Donald
Graphical abstract: Abstract: A series of reversible inhibitors of lysine specific demethylase 1 (LSD1) with a 5-hydroxypyrazole scaffold have been developed from compound7, which was identified from the patent literature. Surface plasmon resonance (SPR) and biochemical analysis showed it to be a reversible LSD1 inhibitor with an IC50 value of 0.23 µM. Optimisation of this compound by rational design afforded compounds with K d values of <10 nM. In human THP-1 cells, these compounds were found to upregulate the expression of the surrogate cellular biomarker CD86. Compound11p was found to have moderate oral bioavailability in mice suggesting its potential for use as an in vivo tool compound.